Publication and methodological trends in creative thinking research in Indonesian biology education - Muhammad Syahrul; Syahran Wael; Ine Arini; Husnaini Bahri (Biosfer: Jurnal Pendidikan Biologi, 2026)
Creative thinking skills have become a central focus in biology education research in Indonesia, reflecting the growing demand for innovative and student-centered learning approaches. However, comprehensive evidence regarding research design and data analysis trends in this field remains limited. This study aims to analyze publication and methodological trends in creative thinking research published in SINTA-accredited biology education journals in Indonesia between 2012 and 2024. A content analysis was conducted on 121 peer-reviewed articles published between 2012 and 2024, focusing on research design, instruments, data analysis techniques, and biological content domains. The results indicate that quantitative and quasi-experimental designs dominate the field, with tests and questionnaires as the most frequently used instruments, while descriptive and inferential statistics remain the primary analytical approaches. These findings suggest the need for greater methodological diversity and deeper integration of biological content contexts, and this study recommends future researchers to adopt mixed-method approaches and advanced analytical techniques to strengthen the rigor and impact of creative thinking research in biology education.